Developing and Implementing Mother-tongue Education Policy in Minority Speech Communities in Nepal: Issues and Challenges (Studies in ELT and Applied Linguistics, 2021)
This paper examines some major issues and challenges in developing and implementing mother-tongue education policy in minority speech communities in Nepal. It also suggests some strategies based on field studies for meeting those challenges. In minority speech communities, constituting more than 55% of total population and speaking around 70 languages, despite attempts made by governmental and non-governmental agencies, multilingual education has not yet become accessible it is mainly due to the lack of operational mechanism in education policy. Till today, thousands of children of non-Nepali speaking communities are compelled to be instructed in Nepali and use the textbooks written in Nepali. This has resulted in class repetition, high dropout and very low quality at primary levels.The case studies made in Western Tamang and Rajbansi have explored a number of challenges as well as some way-outs for effective implementation of mother-tongue education policy in such communities. First and foremost, the roles of mother tongue, Nepali and English have not yet been fully justified. In most of the minority speech communities, there is only sentimental attitude towards their mother tongue. Most of the MLE programmes have been commenced without conducting need assessment (Regmi, 2019). There is a lack of appropriate textbooks and reading materials incorporating local cultures and life crucial knowledge embodied in language. Due to the lack of trained and motivated teachers, programmes so far implemented are also facing the problem of quality maintenance. Thus, a promising and inclusive multilingual education policy should be developed and implemented for maintaining the sustainability of MLE programmes in minority speech communities in Nepal.